Research on the enhancement of mechanical properties of as-HIPed FGH100L nickel-based superalloy via heat treatment - Xiaona Ren; Zhenfan Wang; Yao Wang; Zihao Wang; Weifeng Qi; Xinggang Li; Changchun Ge (Journal of Materials Research and Technology)
Direct hot isostatic pressing (as-HIP) is a near-net forming technology for materials, which not only enables the preparation of complex-shaped parts but also offers excellent uniformity and performance. It has certain advantages in the fabrication of powder metallurgy (PM) superalloy complex parts, while, there is still room for improvement in the performance of as-HIPed PM superalloy parts. In this study, we investigated the strengthening effect of solution treatment and aging treatment on FGH100L formed by as-HIP. The results indicate that when the solution treatment is conducted at 1190 °C for 1 h, with the primary aging time of 4 h and the secondary aging time of 8 h, the as-obtained samples possess excellent comprehensive mechanical properties, which are yield strength of 1182.33 MPa and 1096.84 MPa, ultimate tensile strength of 1611.33 MPa and 1502.62 MPa, ductility of 19.37 % and 16.63 %, at room temperature and 705 °C respectively. Hence, solution strengthening combined with aging strengthening can enhance the comprehensive mechanical properties of as-HIPed FGH100L nickel-based superalloy.